Extenuation in the Penal Code 2015 and Current Issues - Tran, Thi Quynh (H. : ĐHQGHN, 2020)
Extenuation is considered by the Court when issuing a sentence, manifesting the state’s leniency policy and the classification principle of penal liability in the Penal Code of Vietnam, ensuring efficiency and meaning of penalties. On this basis, this Article provides a new scientific approach to the definition of extenuation, analysing contents and levels of extenuation in provisions of the Penal Code 2015 (revised in 2017), examining issues in practical adjudication, and making recommendations on crime prevention and improvement of rehabilitation and re-education of individual and corporate offenders in the current context of the country.